Monitoring the impact of COVID-19 in Myanmar: Agricultural input retailers - June 2020 survey round - Goeb, Joseph; Boughton, Duncan; Maredia, Mywish K.; Zu, A Myint; Synt, Nang Lun Kham (International Food Policy Research Institute, 2020)
Agricultural input retailers play a key role in Myanmar’s agri-food system by supplying farmers with fertilizer, seed, pesticides, and other inputs necessary for successful harvests. Because farm-level input use is an important driver of yields for all major food crops, shocks to the input retail sector have major implications for the welfare of rural households, as well as for their food security. This policy note presents results from round two of a five-round phone survey of agricultural input retailers. Our purpose is to provide data and insights to the Ministry of Agriculture, Livestock, and Irrigation (MOALI) and other agricultural sector stakeholders to assist them in better understanding COVID-19 related shocks to Myanmar’s agricultural input retailers. The round one results emphasized (i) widespread disruptions from the COVID-19 to both input supply and demand, (ii) higher transportation costs leading to higher input prices, and (iii) dramatically lower revenue expectations for retailers in 2020 compared to 2019.1 This note builds on the round one results by (i) exploring the effects of the COVID-19 crisis since the first-round interviews, (ii) tracking sales changes since the first round of the survey, and (iii) providing more detailed information on retailer credit and transportation.